(untitled) (Journal of Dhaka Medical College, 2015)
Background: Contraceptives not only prevent unplanned pregnancy but also enhance the quality of life. Choice of contraceptive varies from person to person. Objectives: To observe the type of contraceptive chosen by women, to determine the sociodemographic status of women sought contraceptive and to detect the pattern of contraceptive selection by women of different age. Methods: It was a cross sectional, observational, descriptive type of study performed at Family Planning Unit of Dhaka National Medical College Hospital, Dhaka, between May 2005 and April 2006. No sampling technique was applied in the study. All clients sought contraceptive methods were recruited for the study purposively. A total 3392 respondents was included in the study. The socio-demographic status and obstetrical history and choice of contraceptives of the clients were recorded and data were analysed. Results: Age of the clients ranges between 16 to 49 years. Among the respondents 95.43% were parous. The educational status showed 44.30% were illiterate and 48.23%, 5.02% 2.41% has got primary, secondary, higher secondary and above education respectively. Among the available methods of contraceptives of this Family Planning Unit, Injectable Depot Medroxy Progesterone Acetate (DMPA) and Combined Oral Contraceptive (COC) pill were chosen by 50.65% (n= 1718) and 40.60% (n=1379) of respondents respectively. Intrauterine contraceptive Device (IUCD) and barrier method was chosen by 4.75% (n=160) and 3.98% (n=135) respondents respectively. It was observed that highest number of the clients was between the age 25 and 34 years. They were found at the top of using each type of contraceptive. The study reveals that a few older women (n=21) sought contraceptives and their choice of contraceptives were confined to COC and Barrier method only. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22704 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 109-113